Digital Marketing Capability and SME Marketing Performance: A Structural Equation Modeling Approach in Emerging Markets - Pinto Jaya; Mashadi Mashadi; Adil Fadillah; Ade Yusdira (Jurnal Aplikasi Bisnis Kesatuan, 2025)
The rapid digitalization of business activities has fundamentally transformed marketing practices among Small and Medium Enterprises (SMEs). While many SMEs have adopted digital platforms, inconsistent performance outcomes suggest that technology adoption alone is insufficient to ensure competitiveness. This study aims to examine the structural relationships among Digital Marketing Capability, Market Orientation, Customer Engagement, and Marketing Performance within SMEs. Drawing upon the Resource Based View and Dynamic Capability Theory, this research proposes that strategic capabilities influence marketing outcomes both directly and indirectly through relational mechanisms. A quantitative cross-sectional survey was conducted involving 250 SME owners and managers in the culinary and fashion sectors in East Java, Indonesia. Data were analyzed using covariance-based Structural Equation Modeling. The findings reveal that Digital Marketing Capability and Market Orientation significantly influence Customer Engagement and Marketing Performance. Furthermore, Customer Engagement partially mediates the relationship between strategic capabilities and performance outcomes. The results highlight that sustainable SME marketing performance depends not merely on digital adoption, but on the development of structured digital competencies and customer-oriented culture. This study contributes to marketing literature by integrating capability, engagement, and performance constructs within a unified SEM framework in an emerging market context. Practically, the findings provide guidance for SME managers and policymakers in designing capability-based digital development strategies.